2016
DOI: 10.32404/rean.v3i4.1186
|View full text |Cite
|
Sign up to set email alerts
|

Utilização De Radiação Gama E Amido De Milho No Armazenamento Pós-Colheita Das Folhas De Couve Manteiga

Abstract: Devido à alta perecibilidade apresentada pelas folhas de couve-manteiga após a colheita, o presente trabalho teve por objetivo avaliar o efeito isolado e combinado da radiação gama e amido de milho visando o prolongamento de sua vida útil. O delineamento experimental utilizado foi o inteiramente casualizado em esquema fatorial 4 x 9 com cinco repetições e os parâmetros teor de clorofila, atividade das enzimas POD e PPO, sólidos solúveis, pH, acidez titulável, perda de massa fresca, murchamento, sabor e qualida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Soil amendments and topdress sulfur rates caused no significant changes in pH and titratable acidity in the collard leaves (Table 2), with an overall mean of pH = 6.24 and titratable acidity = 0.25%. Sanches et al (2016) [37] reported lower pH (5.20) and higher titratable acidity (0.31%) values for curly 'butter collard', which is an evidence of consistency in the results, i.e., higher acidity with lower pH. Pereira et al (2015) [38] evaluated collards produced in an organic system and reported pH of 5.6 and titratable acidity of 0.20%.…”
Section: Soil Amendmentmentioning
confidence: 82%
See 1 more Smart Citation
“…Soil amendments and topdress sulfur rates caused no significant changes in pH and titratable acidity in the collard leaves (Table 2), with an overall mean of pH = 6.24 and titratable acidity = 0.25%. Sanches et al (2016) [37] reported lower pH (5.20) and higher titratable acidity (0.31%) values for curly 'butter collard', which is an evidence of consistency in the results, i.e., higher acidity with lower pH. Pereira et al (2015) [38] evaluated collards produced in an organic system and reported pH of 5.6 and titratable acidity of 0.20%.…”
Section: Soil Amendmentmentioning
confidence: 82%
“…The different soil amendments and topdress sulfur rates had no influence on soluble solids contents of commercial collards, with an overall mean of 9.28 ºBrix (Table 2). Lower values were found by Sanches et al (2016) [37] in curly 'butter collard' (7.8 °Brix), by Salata et al (2014) [34] in minimally processed cabbage immediately after harvest (5.65 °Brix), and by Godoy et al (2012) [35] in cauliflower (6.58 °Brix). This trait can be influenced by various production factors such as genetic material, soil type, climate, and crop cultural practices.…”
Section: Soil Amendmentmentioning
confidence: 91%
“…Vários fatores podem influenciar nessa característica, como material genético utilizado, tipo de solo, condições meteorológicas e os tratos culturais, visto que os maiores teores de sólidos solúveis observados indicam maior doçura ao vegetal. Sanches et al (2016), observaram valores de 7,8 °Brix em couve de folha manteiga verde crespa ao avaliarem a utilização da radiação gama e do amido de milho na conservação pós-colheita das folhas; no primeiro dia de avaliação, os valores são semelhantes aos 80 DAT desta pesquisa. Primak et al (2016), ao avaliarem o efeito de diferentes concentrações de ácido salicílico e períodos de armazenamento na conservação pós-colheita de couve folhas, observaram valores superiores aos desta pesquisa, com teores de 10,2 °Brix para couve de folha no tempo 0; estas folhas utilizadas na avaliação foram colhidas aos 75 DAT.…”
Section: Resultsunclassified
“…Due to its metabolism, kale leaf has high perishability, having as indicators yellowing and loss of turgor causing a consequent short postharvest period (Sanches et al 2016). For this reason, methods that increase shelf life without changing the taste and nutritional qualities and at the same time are health and safe have been sought.…”
Section: Highlighted Conclusionmentioning
confidence: 99%